The role of agribusiness firms in agricultural research: The case of China - Zhang, Huije; Fan, Shenggen; Qian, Keming (2006)
In the last two decades public funding for agricultural research and development (R&D) in China reached a plateau causing productivity within the agricultural sector to diminish. Over this period there has been a rapid establishment of agribusiness firms, which have injected private funds into agricultural R&D and have offered farmers new opportunities to increase productivity and income. Importantly, these firms are changing their role in agricultural R&D and technology adoption, which has significantly affected the Chinese agricultural research system. Agribusiness firms are positioned to play a more significant role in agricultural R&D investment in China creating an integrated framework of agricultural scientific and technological expertise.